Outdoor activities and contact with nature in the Portuguese context: a comparative study between children’s and their parents’ experiences - Almeida, António (2021)
Several studies in the Scandinavian and Anglo-Saxon countries have shown a decline in outdoor activities and contact with nature during childhood. In Latin countries, these studies are still missing. A total of 562 urban children from Lisbon (Portugal) and 303 of their parents took part in the present study, which mainly aimed to compare the intergenerational engagement in outdoor activities. The results showed a decrease in children’s outdoor activities during the weekdays, weekends and summer holidays. Activities like picking berries, collecting rocks and fossils or climbing trees appear to be rarely performed nowadays. Furthermore, the results suggested that schools are no longer playing a role in promoting outdoor activities and children are spending their leisure time indoors, using technological devices or going shopping. Finally, the decline in outdoor activities seems to affect boys and girls equally. Several implications are discussed and recommendations for parents, teachers and politicians are proposed.